Task Completion Platform: A self-serve multi-domain goal oriented dialogue platform - Crook, Paul A.; Marin, Alex; Agarwal, V.; Aggarwal, K.; Anastasakos, T.; Bikkula, R.; Boies, D.; Celikyilmaz, Asli; Chandramohan, S.; Feizollahi, Z.; Holenstein, R.; Jeong, M.; et al. (ACL - Association for Computational Linguistics, 2016)
We demonstrate the Task Completion Platform (TCP); a multi-domain dialogue platform that can host and execute large numbers of goal-orientated dialogue tasks. The platform features a task configuration language, TaskForm, that allows the definition of each individual task to be decoupled from the overarching dialogue policy used by the platform to complete those tasks. This separation allows for simple and rapid authoring of new tasks, while dialogue policy and platform functionality evolve independent of the tasks. The current platform includes machine learnt models that provide contextual slot carry-over, flexible item selection, and task selection/switching. Any new task immediately gains the benefit of these pieces of built-in platform functionality. The platform is used to power many of the multi-turn dialogues supported by the Cortana personal assistant.